2018
DOI: 10.1109/access.2018.2816916
|View full text |Cite
|
Sign up to set email alerts
|

Power Control and Resource Allocation for Multi-Cell OFDM Networks With Load Coupling

Abstract: In this paper, we study the power control and resource allocation problem in downlink orthogonal frequency division multiplexing networks, where mutual interference exists among cells. This mutual relation is characterized by the load coupling model. Both cell load and transmit power, where cell load measures the average proportion of resource usage in the cell, interact via the coupling model. We consider three kinds of problems, sum power minimization, sum rate maximization, and sum energy efficiency maximiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…(11) is a nonconvex optimization problem. We use the suboptimal linear programming method proposed in [44] as the benchmark.…”
Section: High Complexity Problemmentioning
confidence: 99%
See 3 more Smart Citations
“…(11) is a nonconvex optimization problem. We use the suboptimal linear programming method proposed in [44] as the benchmark.…”
Section: High Complexity Problemmentioning
confidence: 99%
“…In [44], the problem is converted to a convex optimization problem and solved by sequential least squares programming (SLSQP) optimization.…”
Section: High Complexity Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…In HetNets, the load (average utilization level of the time-frequency resource blocks) conditions in macro BSs and small BSs are in most case coupled. A realistic loadcoupled model was proposed in [17]- [20], which took into account the effect of the load conditions in terms of inter-cell interference. In [21], it was shown that this load-coupled model well models a multi-cell network.…”
Section: Introductionmentioning
confidence: 99%